BioCleanze detergent / Arissa Saffiya Mohd Rosyidi ... [et al.] - Mohd Rosyidi, Arissa Saffiya; Yap Xin Lin, Cassandra; Abdul Rahim, Irfan Ayisy; Mohd Hisham, Nisha Shahira; Amran, Nur Farhana (2025)
BioCleanze partnership is an innovative, eco-conscious company based in Selangor, Malaysia, specializing in providing eco-friendly and sustainable detergents. Our mission is to create eco-friendly detergent solutions that ensure effective cleaning and promote environmental sustainability. With a vision to become the leading provider of biodegradable cleaning products in Southeast Asia, BioCleanze is set to revolutionize the detergent industry with its sustainable approach. Our product is a customizable, eco-certified detergent made entirely from plant-based ingredients and natural enzymes. Free from phosphate and harsh chemicals, the detergent is safe for the skin, dermatologist-tested, and packaged using recyclable materials. It has obtained notable certifications from MyHIJAU and SIRIM Eco-Labelling, ensuring credibility and alignment with global sustainability standards.